Slithering Through the Bone Marrow: Loiasis in a Patient With Human T-Cell Leukemia Virus-1-Associated Adult T-Cell Lymphoma. (28th October 2020) - Boodman, Carl; Marko, Daniel; Keynan, Yoav
Abstract: Loiasis is a filarial disease endemic to areas of Central and West Africa. We present a case of Loa loa microfilaremia in a patient with HTLV-1-related adult T-cell lymphoma. This case may suggest the possible role of cellular immunity in controlling microfilaria burden. Abstract : Loiasis is a filarial disease endemic to areas of Central and West Africa. We present a case of Loa loa microfilaremia in a patient with HTLV-1-related adult T-cell lymphoma. This case may suggest the possible role of cellular immunity in controlling microfilaria burden.